The Ubiquitin-Proteasome System in Apoptosis and Apoptotic Cell Clearance - Yuan, Lei; Li, Peiyao; Zheng, Qian; Wang, Hui; Xiao, Hui (Frontiers in Cell and Developmental Biology, 2022)
Ubiquitination, a critical post-translational modification of proteins, refers to the covalent attachment of ubiquitin to the substrate and is involved in various biological processes such as protein stability regulation, DNA damage repair, and apoptosis, among others. E3 ubiquitin ligases are essential enzymes of the ubiquitin pathway with high substrate specificity and precisely regulate specific proteins' turnover. As one of the most well-studied forms of programmed cell death, apoptosis is substantially conserved across the evolutionary tree. The final critical stage in apoptosis is the removal of apoptotic cells by professional and non-professional phagocytes. Apoptosis and apoptotic cell clearance are crucial for the normal development, differentiation, and growth of multicellular organisms, as well as their association with a variety of inflammatory and immune diseases. In this review, we discuss the role of ubiquitination and deubiquitination in apoptosis and apoptotic cell clearance.